Grupos educativos para gestantes: formando e educando para a promoção da saúde - Alves, Bianca de Oliveira (2018)
Introduction: Education groups are a great ally to fill the prenatal care gaps, promoting listening and prioritizing the issues that further away them from that period. Objective: To create an educational group of permanent pregnant women in the Nursing Course of the Anhanguera College of Sorocaba, counting on the participation of nursing trainees. To know the perception of these pregnant women and students participating in the experience. Methods: This was an exploratory, descriptive, qualitative, participatory research study of two distinct groups: 8 students and 14 pregnant women, both from a Sorocaba / SP college. At the end of the last meeting, the participants were interviewed based on an open question for each group. Conclusion: The methodology used in the meetings promoted a rich exchange of experiences in a welcoming environment that contemplated listening, decreased fears and anxieties, appreciated popular knowledge and exalted the collective construction of it. It revealed an important and fertile moment for the students' learning to socialize the experiences of the pregnant women, a contact with the reality different from those methods of learning used in their academic formation. The stimulus to change posture in the face of knowledge, the growing involvement in this process, the importance of exchanging experiences in learning and watching captivated students. The contact with the reality of the pregnant women allowed to extrapolate the walls of the classrooms, to develop nurses' competences, articulating theory and practice, planning and intervening. The results confirm the importance and necessity of keeping it active, integrating teaching / assistance and service, in line with the SUS premises and the curricular guidelines of nursing higher education